IMPACT OF ADHD ON ORAL HEALTH IN CHILDREN – A LITERATURE REVIEW - Michalina Pastuszka; Aleksandra Małgorzata Obarzanek; Kamil Nieroda; Michał Nowak; Zbigniew Klimek; Olaf Jadanowski; Natalia Nowek; Julia Joanna Bijata; Dominika Miśta; Julia Tetelewska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurobehavioral disorders and has been suggested to be associated with poorer oral health in children. Difficulties with concentration and a tendency to become easily bored may contribute to inadequate oral hygiene practices and malocclusion. Additionally, hyperactivity and impulsivity often lead to frequent snacking on sweets, which further increases the risk of dental problems in this population. This study aimed to summarize the current knowledge on the relationship between ADHD and oral health, particularly focusing on the prevalence of dental caries, gingival bleeding, and malocclusion. Previous research indicates that children with ADHD are at an elevated risk of developing dental caries and may require more frequent dental visits compared to their peers without ADHD. However, further studies are needed to better understand these correlations and to establish evidence-based preventive and therapeutic strategies.Results: ADHD may negatively affect the development of dental caries, gingival bleeding, and malocclusion in children. Children with this condition tend to have higher plaque (PI) and DMFT/dmft indices and are more likely to exhibit parafunctional habits. Diet and parental awareness also play a crucial role, as parents need to actively support and guide their children in maintaining proper oral hygiene.Materials and methods: reviewing recent literature research up to 5 years ago based PubMED, Google scholar reaserch based on following key words: Attention deficit heperactivity disorder, oral health, gingival bleeding, bruxism.